Analisis Kendali Kecepatan Motor Induksi 3 Fasa Dengan Metode Direct Torque Control (DTC) Berbasis PID Kontrol - Mokh. Suseno Aji Sari; Hadi Suyono; Abraham Lomi (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2020)
This research was conducted to regulate the three phase induction motor speed regulation system. Changes in load on the motor affect the motor speed response so it does not match the set point speed. This study uses the Direct Torque Control (DTC) method in regulating the speed of an induction motor. The DTC method is a vector control method that is directly assigned to the inverter. DTC method in controlling speed based on Proportional Integral Differential (PID) control. Determination of PID tunning using two methods, namely, ziegler-nichols and cohen-coon method. The ziegler-nichols method have overshoot speeds starting at 0.8% of the setpoint, whereas using the cohen coon method there is no overshoot and the speed at stable conditions matches the setpoint.